Conserved protein targets for developing pan-coronavirus drugs based on sequence and 3D structure similarity analyses. (June 2022) - Ma, Minfei; Yang, Yanqing; Wu, Leyun; Zhou, Liping; Shi, Yulong; Han, Jiaxin; Xu, Zhijian; Zhu, Weiliang
Abstract: There are 7 known human pathogenic coronaviruses, which are HCoV-229E, HCoV-OC43, HCoV-NL63, HCoV-HKU1, MERS-CoV, SARS-CoV and SARS-CoV-2. While SARS-CoV-2 is currently caused a severe epidemic, experts believe that new pathogenic coronavirus would emerge in the future. Therefore, developing broad-spectrum anti-coronavirus drugs is of great significance. In this study, we performed protein sequence and three-dimensional structure analyses for all the 20 virus-encoded proteins across all the 7 coronaviruses, with the purpose to identify highly conserved proteins and binding sites for developing pan-coronavirus drugs. We found that nsp5, nsp10, nsp12, nsp13, nsp14, and nsp16 are highly conserved both in protein sequences (with average identity percentage higher than 52%, average amino acid conservation scores higher than 5.2) and binding pockets (with average amino acid conservation scores higher than 5.8). We also performed the similarity comparison between these 6 proteins and all the human proteins, and found that all the 6 proteins have similarity less than 25%, indicating that the drugs targeting the 6 proteins should have little interference of human protein function. Accordingly, we suggest that nsp5, nsp10, nsp12, nsp13, nsp14, and nsp16 are potential targets for pan-coronavirus drug development. Graphical abstract: Image 1 Highlights: The nine proteins of coronavirus were found to be relatively conserved. Six of the nine conservative proteins have highly conserved binding pockets. Drugs targeting 6 conserved proteins have little interference with human proteins. The 6 proteins are potential drug targets for pan-coronavirus drug development.